Conference The Politics Of Culture. Perspectives of Stateless Nationalities and Ethnic Groups.: April 9-10, 2010, Warsaw, Poland. - Vaňková, Markéta (Lidé města, 2010)
The international conference with almost thirty speakers was organised by Professor Nowicka-Rusek under the patronage of the Institute of Social Studies of the University of Warsaw. The aim of the conference was to focus, from various points of view, on stateless ethnic groups and nationalities which try to negotiate and vindicate the legitimization of their very existence and their (mostly cultural language) demands in today´s world. The conference had seven thematic sessions in which scholars from several social science disciplines, mostly sociology, anthropology, ethnology, and political science, addressed the audience.